The Role of the Legal Aid Institute of Lancang Kuning University in Law Enforcement - Samariadi; Ummah, Kuntum Khaira; Kurniawan, Jupri Dwi; Sari, Indah; Putri, Megawati; Daffa, Baihaqqi; Mirza, Averroes; Dirmansyah, Irud; Aisyani, Neirista (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research examines the role of the Legal Aid Institute of Lancang Kuning University in providing legal protection and ensuring equal treatment under the law, particularly for underprivileged individuals. It highlights the importance of legal aid in promoting justice.Method: A qualitative approach was used, gathering data through interviews, document analysis, and observations of the institute’s activities. Content analysis was applied to assess the effectiveness of its legal services.Practical Applications: The research demonstrates the importance of professional legal aid for underprivileged communities, showing how the institute's work in criminal and civil cases improves access to justice.Conclusion: The Legal Aid Institute plays a vital role in promoting equal justice, particularly for marginalized groups, through legal representation and advocacy in Riau, contributing to law enforcement and human rights protection.